Optimal selection of composite layup considering the fuselage crashworthiness - Dong Wang; Lin Chen; Shaohua Ji; Hua Cao; Meirong Xiong; Changchun Wang; Ju Qiu (Composites Part C: Open Access)
This paper will introduce four main sections of content. Firstly, starting from the crashworthiness simulation analysis and test of simple columns, this paper examines the convergence of dynamic simulation models and the rationality of the selection of dynamic parameters. Secondly, after the multi-objective optimization analysis of the fuselage skin layer model, the optimal selection of skin layers is carried out. Under the condition of meeting the static working condition requirements, the Double-double (DD) layer has better dynamic characteristics and lighter mass. Thirdly, the verification of the crashworthiness analysis of the middle fuselage shows that the DD layer still has better dynamic characteristics, lighter mass, and better stability under the condition of meeting the static working condition requirements. Fourthly, by analyzing the constitutive relationship of the fuselage skin and programming analysis, the composite skin with the same quality has a higher bending-torsion stiffness and bending-torsion coupling stiffness with DD layers.